The Effect of Non-Compliance with Medication on Multidrug Resistant of Tuberculosis - Widya Kurnianingsih; Didik Gunawan Tamtomo; Bhisma Murti (Journal of Epidemiology and Public Health, 2020)
Background: Multidrug Resistant Tubercu